GABAergic Neuronal Precursor Grafting: Implications in Brain Regeneration and Plasticity. (20th June 2011) - Alvarez Dolado, Manuel; Broccoli, Vania
Abstract : Numerous neurological disorders are caused by a dysfunction of the GABAergic system that impairs or either stimulates its inhibitory action over its neuronal targets. Pharmacological drugs have generally been proved very effective in restoring its normal function, but their lack of any sort of spatial or cell type specificity has created some limitations in their use. In the last decades, cell-based therapies using GABAergic neuronal grafts have emerged as a promising treatment, since they may restore the lost equilibrium by cellular replacement of the missing/altered inhibitory neurons or modulating the hyperactive excitatory system. In particular, the discovery that embryonic ganglionic eminence-derived GABAergic precursors are able to disperse and integrate in large areas of the host tissue after grafting has provided a strong rationale for exploiting their use for the treatment of diseased brains. GABAergic neuronal transplantation not only is efficacious to restore normal GABAergic activities but can also trigger or sustain high neuronal plasticity by promoting the general reorganization of local neuronal circuits adding new synaptic connections. These results cast new light on dynamics and plasticity of adult neuronal assemblies and their associated functions disclosing new therapeutic opportunities for the near future.